Acquisition and Utilization of Information About Alcohol Use in Pregnancy Among Australian Pregnant Women and Service Providers. (4th October 2013) - Loxton, Deborah; Chojenta, Catherine; Anderson, Amy E.; Powers, Jennifer R.; Shakeshaft, Anthony; Burns, Lucy
Abstract : Introduction: Because of an unknown safe level of alcohol consumption during pregnancy and inconsistent alcohol guidelines for pregnant women, it is unclear what information is being circulated with regard to alcohol use and pregnancy. This study aimed to explore how pregnant women and service providers acquire and utilize information about alcohol use during pregnancy. Methods: This qualitative study involved 10‐minute semistructured interviews with 74 mothers of young children and focus groups with 14 service providers in urban and rural areas of New South Wales in 2008 and 2009. Mothers were asked about their use of pregnancy‐related services, social support, and their perceptions about advice they received about alcohol use during pregnancy. Service providers were asked about what they knew about recommended alcohol use during pregnancy, how they knew it, and how they communicated this information to pregnant clients. Results: Women and service providers expressed uncertainty about what the alcohol recommendations were for pregnant women. Health care providers were inclined to discuss alcohol use with women they perceived to be high risk but not otherwise. Women felt pressure to both drink and not drink during their pregnancies. Those who drank discounted abstinence messages and reported a process of internal bargaining on issues such as the stage of their pregnancy and the type of beverages they consumed. Those who abstained did so mainly because they were afraid of being held responsible for any problems with their pregnancies or infants that might have occurred from drinking. Discussion: Confusion surrounding the recommendations regarding alcohol use during pregnancy, inconsistency in addressing alcohol use with pregnant women, information overload, and a perceived culture of drinking appear to contribute to the high proportion of Australian women drinking during pregnancy.